2018
DOI: 10.1063/1.5001330
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of oscillating plates in viscous fluids: Qualitative and quantitative analysis of the flow physics and hydrodynamic forces

Abstract: In this paper, we present a comprehensive experimental study on harmonic oscillations of a submerged rigid plate in a quiescent, incompressible, Newtonian, viscous fluid. The fluid-structure interaction problem is analyzed from both qualitative and quantitative perspectives via a detailed particle image velocimetry (PIV) experimental campaign conducted over a broad range of oscillation frequency and amplitude parameters. Our primary goal is to identify the effect of the oscillation characteristics on the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The fluid motion along the length of the cantilever is essentially just upward or downward, and the velocity component in the forward direction is negligible. This is somewhat reminiscent of the flow regime observed by Shrestha et al [32], where isolated attached vortices are observed at low amplitudes and frequencies with no significant convection on the lateral side of a vibrating cantilever. We previously observed poor performance of piezoelectric fans operating in this regime [46].…”
Section: Non-propagating Vortex Regimesupporting
confidence: 60%
See 2 more Smart Citations
“…The fluid motion along the length of the cantilever is essentially just upward or downward, and the velocity component in the forward direction is negligible. This is somewhat reminiscent of the flow regime observed by Shrestha et al [32], where isolated attached vortices are observed at low amplitudes and frequencies with no significant convection on the lateral side of a vibrating cantilever. We previously observed poor performance of piezoelectric fans operating in this regime [46].…”
Section: Non-propagating Vortex Regimesupporting
confidence: 60%
“…More specifically, they observed that the transition from von Kármán to reverse von Kármán in a non-zero freestream velocity medium around a pitching airfoil takes place at a constant tip characteristic velocity Af for a fixed cord length. Shrestha et al [32] reported a critical value of Rec ~ 21 for the transition from the symmetric to asymmetric vortex regime for the lateral vortex generation of a submerged flat cantilever plate in water. In many applications, such as cooling enhancement using piezoelectric fans, the average flow generation in the streamwise direction due to the cantilever vibrations is of great interest.…”
Section: Regime Map and Correlation With Airflow Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…That allows to use a simplified quasi-two dimensional model of interaction between a beam and a gas, according to which the aerodynamic forces acting on each cross-section of the beam can be considered as a result of the planar flow past a section. This model is widely used in many studies [3,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Eastman, Kiefer & Kimber (2012) studied thrust force generation by vibrating cantilever plates and proposed a correlation between the thrust and the vibration amplitude and frequency. Shrestha, Ahsan & Aureli (2018) studied the lateral vortex shedding in a pitching plate with a fixed geometry using particle image velocimetry (PIV) visualizations and proposed a 2-D vortex regime map to describe the observed patterns. These patterns were correlated with aerodynamic drag forces on the plate.…”
mentioning
confidence: 99%